2019
DOI: 10.1159/000497488
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR-192 Is Related to Tubulointerstitial Lesion and Short-Term Disease Progression in IgA Nephropathy

Abstract: Background/Aims: Clinical manifestation and renal histology serve as the current “gold standard” for evaluation of renal lesions in IgA nephropathy. MiR-192 is regarded as a potential noninvasive biomarker for kidney disease. We sought to elucidate a relationship between intrarenal, serum, and urinary exosomal miR-192 with renal lesions and disease progression in IgA nephropathy. Methods: Serum and urinary exosomal miR-192 were detected and correlated with clinical and pathological parameters from consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…miR-192 prevented renal tubulointerstitial fibrosis in DN rat model by targeting early growth response factor 1 (Egr1) (Liu et al, 2018a). In IgA nephropathy (IgAN), lower serum exosomal miR-192 in IgAN patients correlated with more severe tubular atrophy, interstitial inflammation, and fibrotic tendency (Fan et al, 2019). In addition, urinary miR-192-5p was proposed as a potential biomarker of ischemia/reperfusion-induced kidney injury (Zou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…miR-192 prevented renal tubulointerstitial fibrosis in DN rat model by targeting early growth response factor 1 (Egr1) (Liu et al, 2018a). In IgA nephropathy (IgAN), lower serum exosomal miR-192 in IgAN patients correlated with more severe tubular atrophy, interstitial inflammation, and fibrotic tendency (Fan et al, 2019). In addition, urinary miR-192-5p was proposed as a potential biomarker of ischemia/reperfusion-induced kidney injury (Zou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The degree of tubulointerstitial scarring correlated with miR-205 expression, whereas glomerulosclerosis correlated with miR-192 expression. However, in another study, miR-192 was lower in IgAN patients and it correlated with GFR [42]. Patients with lower intrarenal miR-192 levels had a higher degree of interstitial fibrosis, more severe lesions in tubular atrophy, and interstitial inflammation [42].…”
Section: Association With the Severity Of Renal Damagementioning
confidence: 90%
“…However, in another study, miR-192 was lower in IgAN patients and it correlated with GFR [42]. Patients with lower intrarenal miR-192 levels had a higher degree of interstitial fibrosis, more severe lesions in tubular atrophy, and interstitial inflammation [42]. MiR-233 in glomerular endothelial cells (GEnCs) in IgAN patients correlated with urine protein level, urine erythrocyte count, blood creatinine level, glomerular endothelial proliferation score, and glomerular crescent rate [56].…”
Section: Association With the Severity Of Renal Damagementioning
confidence: 96%
See 1 more Smart Citation
“…In a similar vein, Fan et al [92] sought to establish a potential association between the intrarenal expression of miR-192 with serum and urinary exosome levels in IgAN patients compared to healthy subjects. They confirmed that intrarenal miR-192 expression correlated with serum levels, eGFR, and with severe interstitial lesions, tubular atrophy and interstitial inflammation.…”
Section: Serum and Plasmamentioning
confidence: 99%